Semiotics of cartographic discourse: Analysis of the 1613 map of Grand Duchy of Lithuania - Bružienė , Jovita (Semiotika, 2013)
Reading of a map is defined by two different ways of looking: firstly a synoptic gaze grasps the totality of a map, then it locates itself in some particular place and begins to travel – follows linear elements that invite and lead the eye. The reading direction is identified according to fragmentation, topology, framing, central places and layering of the elements. Thus a semiotic approach to a cartographic discourse should begin with an analysis of the plastic level. The reading direction on the 1613 map of Grand Duchy of Lithuania can be identified to start in the corner of the Baltic Sea. The route chosen denies new borders of the country and restores the old boundaries. The subject is motivated by modalities of having to do (figuratively represented by the wind) and wanting (figuratively – rivers). The former is replaced with the latter by establishing the contract between the subject and the sender. The journey ends in the territory of the Black sea, near the mouth of the Bug river – an utopian space related to the cosmic plane and historical past of Lithuania.By following the itinerary the subject passes from one space to another, he crosses forbidden borders. The shift through the border of the semantic field is qualified as an event – unit of plot construction (according to Lotman). By implementing the narrative program the subject negates the order of the plotless text; his movement forms the plot – the narrative. The spatial organization of a cartographic discourse is defined by its conceptual and visual aspects. The former is being related to the nature of space (being): the mapped milieu is usually reduced to a network of points, the distance between points is desemantized. When the being is combined with the appearing the mapped space matches a schema: a territory is seen from above, nothing is hidden, but only relevant elements appear in this view, the space between them is empty. In the map analyzed this scheme is implemented in the depiction of the Black Sea. An orthogonal depiction is related to operation of disengagement, whereas perspective view signifies the opposite. Some  elements  of  the  map  are  represented  in  perspective,  although  the space  encoded  in  these  representations  belongs  to  the  network  regime.  The space between the points in these depictions is not only desemantized, but also eliminated. The network is so dense that it looks like a tissue. These depictions (city views in the map) can be called perspective maps. The narrative program implements a shift from the space of tissue (the Baltic Sea is represented in mimetic manner) to the space of network (the Black Sea). These opposite terms are linked by the medium term of perspective map, a dense tissue (city views). The performance of the subject is associated with the orthogonal view – this witnesses the authority and value of cartographic discourse.The analysis of the written description of Lithuania appended to the map reveals that a written text can produce a cartographic effect as well. By simulating a synoptic and traveling gaze and devaluing the top category (i.e. – projecting described view onto the surface) it competes with the map and even attempts to transform its meaning.
Keywords: Semiotic approach; cartographic discourse; cartographic effect; desemantization